MEMINDAI PENERAPAN BIMBINGAN DAN KONSELING MULTIKULTUR DI SMA NEGERI 1 PALANGKARAYA - Bunu, Helmuth Y (Widya Wacana: Jurnal Ilmiah, 2016)
The purpose of this study is to identify the implemantation of Guidance and Counseling inHigh School state 1 Palangkaraya. This study used a qualitative approach. Informants of thisstudy is BK teacher, Headmaster, Teacher, OSIS and School committee, Data were collectedusing the sets include participatory observation, in depth interviewsand analisys with four stage.Data in qualitative reseach phase of Milles and Hubermann. Starting from colection of data,data reduction, data classification and conclusions. The results of reseach in general are: 1) thepurpose of multicultural counseling services, is providing assistance to students to address theissue properly. 2) The types of counseling services include helping clients develop politebehavior, helping to overcome anxiety, explore the potential of students. 3) Specialcharacteritics applied by providing individual counseling services. 4) Counseling servicemulticulture have many media make the most of the existing counselingKeywords: Guidance and Counseling, Multiculture, Scanning, Service